Sposoby prezentacji sekt na przykładzie wybranych filmów [The presentation of sects in selected films] - Hryciuk, Dariusz (Biuletyn Edukacji Medialnej [Media Education Bulletin], 2009)
In the article Dariusz Hryciuk writes about how movies present sects and newly formed religious groups. This motif is not undertaking in the cinema often, but sometimes directors make use of a sect to explain an influence of a small group on the society. Author used six films to reflect on this subject: The Skulls (2000) directed by Rob Cohen, The Skulls 2 (2002) directed by Joe Chappelle, The Skulls 3 (2003) directed by J. Miles Dale, Devil’s Prey (2001) directed by Bradford May, Believers (2007) directed by Daniel Myrick, The Ninth Gate (1999) directed by Roman Polanski. All films show a sect as a dangerous group. All members are manipulated by a leader. Usually the leader is a charismatic person, who wants to take control of all parts of life of his believers. Leader can do everything with the members of his group, even force them to commit suicide.
https://katalog.adlr.link/Record/ai-53-208817